The green transformation of the European maritime sector: Six tricks to support sustainable cruise shipbuilding - Aro Elisa; Haaja Eini (Centrum Balticum Foundation, 2025)
This report explores the current state of sustainable industrial transformation in the maritime industry by mirroring the increasing number of respective policies, strategies and regulations with the views of the industry representatives. The report is divided into two parts; the first one looks into the policies, regulations and incentives that drive green transformation in the maritime industry. The second part builds on empirical data collected among maritime industry firms and industry association representatives, highlighting the opportunities and challenges currently experienced within the business field concerning green transition. Building on the findings in both parts, the report concludes with recommendations for policymakers—the six tricks—to better pursue and guide sustainability transformation in the maritime industry in general and in cruise shipbuilding in particular.